Genomic variation among closely related Vibrio alginolyticus strains is located on mobile genetic elements - Chibani, Cynthia Maria; Roth, Olivia; Liesegang, Heiko; Wendling, Carolin Charlotte (BMC genomics, 2020)
Species of the genus Vibrio, one of the most diverse bacteria genera, have undergone niche adaptation followed by clonal expansion. Niche adaptation and ultimately the formation of ecotypes and speciation in this genus has been suggested to be mainly driven by horizontal gene transfer (HGT) through mobile genetic elements (MGEs). Our knowledge about the diversity and distribution of Vibrio MGEs is heavily biased towards human pathogens and our understanding of the distribution of core genomic signatures and accessory genes encoded on MGEs within specific Vibrio clades is still incomplete. We used nine different strains of the marine bacterium Vibrio alginolyticus isolated from pipefish in the Kiel-Fjord to perform a multiscale-comparative genomic approach that allowed us to investigate [1] those genomic signatures that characterize a habitat-specific ecotype and [2] the source of genomic variation within this ecotype. We found that the nine isolates from the Kiel-Fjord have a closed-pangenome and did not differ based on core-genomic signatures. Unique genomic regions and a unique repertoire of MGEs within the Kiel-Fjord isolates suggest that the acquisition of gene-blocks by HGT played an important role in the evolution of this ecotype. Additionally, we found that ~ 90% of the genomic variation among the nine isolates is encoded on MGEs, which supports ongoing theory that accessory genes are predominately located on MGEs and shared by HGT. Lastly, we could show that these nine isolates share a unique virulence and resistance profile which clearly separates them from all other investigated V. alginolyticus strains and suggests that these are habitat-specific genes, required for a successful colonization of the pipefish, the niche of this ecotype. We conclude that all nine V. alginolyticus strains from the Kiel-Fjord belong to a unique ecotype, which we named the Kiel-alginolyticus ecotype. The low sequence variation of the core-genome in combination with the presence of MGE encoded relevant traits, as well as the presence of a suitable niche (here the pipefish), suggest, that this ecotype might have evolved from a clonal expansion following HGT driven niche-adaptation.